CRYPTOCURRENCY AND DIGITAL MARKETING: LINKING FINANCIAL INNOVATION TO BUSINESS PERFORMANCE - Jovanka Arnelita; Glen Bagasta Simanjuntak; Dompak Pasaribu; Victor Maruli Pakpahan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
The development of financial technology, especially cryptocurrency and blockchain, has had a significant impact on various sectors, including digital marketing. The integration of cryptocurrency into digital marketing strategies provides new opportunities to improve marketing effectiveness and efficiency, build transparency, and strengthen relationships between companies and consumers. This study aims to explore how cryptocurrency and blockchain technology can be optimized in digital marketing to support business performance. The results show that blockchain technology enables more secure data management, transparent transaction management, and token-based loyalty programs that are attractive to consumers. In addition, the use of cryptocurrency in transactions can speed up the payment process, increase customer engagement, and strengthen brand loyalty. However, there are challenges in terms of regulation, consumer adoption of technology, and the need for specialized expertise in blockchain technology. This study provides an important overview of the potential and challenges of cryptocurrency integration in digital marketing and business performance, as well as providing practical advice for companies in implementing this technology.